2014
DOI: 10.3111/13696998.2014.903122
|View full text |Cite
|
Sign up to set email alerts
|

Quality-adjusted survival with combination nab-paclitaxel + gemcitabine vs gemcitabine alone in metastatic pancreatic cancer: a Q-TWiST analysis

Abstract: There are limitations to Q-TWiST analyses, e.g., imprecision when defining duration/severity of TOX and lack of prospective collection of utilities. This analysis addressed these issues via sensitivity analyses and conservative assumptions to show that nab-paclitaxel + gemcitabine results in statistically significant and clinically important gains in quality-adjusted survival, when compared to gemcitabine alone, in treatment-naive metastatic pancreatic adenocarcinoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…On the other hand, quality of life was not assessed in the MPACT trial. In contrast, GNP showed significant improvement in quality-adjusted survival in comparison to gemcitabine alone using the Quality-Adjusted Time Without Symptoms or Toxicities (Q-TWiST) methodology, despite the limitations of the Q-TWiST analysis and the lack of prospective quality of life data from the MPACT trial[8]. …”
Section: Toxicity and Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, quality of life was not assessed in the MPACT trial. In contrast, GNP showed significant improvement in quality-adjusted survival in comparison to gemcitabine alone using the Quality-Adjusted Time Without Symptoms or Toxicities (Q-TWiST) methodology, despite the limitations of the Q-TWiST analysis and the lack of prospective quality of life data from the MPACT trial[8]. …”
Section: Toxicity and Quality Of Lifementioning
confidence: 99%
“…These modifications successfully maintained the efficacy of the drugs while significantly decreasing the toxicity profile (decreased neutropenia, vomiting and fatigue). Additional exploratory analyses of the MPACT trial showed that patients who had dose delays or reductions (71% and 41%, respectively) had better outcomes[8]. These practical changes are capable of modifying the tolerance profile of the drugs while preserving efficacy.…”
Section: Toxicity and Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…A recent analysis assessing nab-paclitaxel plus gemcitabine combination treatment vs gemcitabine-only in first-line mPAC (Reni et al , 2014) found a 21% relative improvement in Q-TWiST in favour of the combination treatment over gemcitabine-only treatment. The Q-TWiST improvement observed in the current analysis for nal-IRI+5-FU/LV ( vs 5-FU/LV) was 24%.…”
Section: Discussionmentioning
confidence: 99%
“…In recent phase III trials for metastatic pancreatic cancer, fluorouracil plus leucovorin plus irinotecan plus oxaliplatin (FOLFIRINOX) and gemcitabine plus albumin-bound paclitaxel (nab-paclitaxel) showed a clear benefit with respect to OS compared with gemcitabine alone 1 2. FOLFIRINOX also showed delayed HRQOL deterioration compared with gemcitabine alone,3 while gemcitabine plus nab-paclitaxel was associated with longer quality-adjusted survival than gemcitabine alone based on non-patient-reported health utilities 4. However, because of their associated toxicities,1 2 these two regimens require a good patient performance status and close monitoring 5 6.…”
Section: Introductionmentioning
confidence: 99%